Penerapan E-Learning Sebagai Media Pembelajaran Dalam Meningkatkan Mutu Pendidikan - Dewi Irmawati (MANAJEMEN INFORMATIKA, 2010)
eLearning or electronic learning is now increasingly recognized as one of the ways to overcome the problems of education, both in developed countries and in developing countries. Many people use different terms with e-learning, but in principle e-learning is learning to use electronic services as a tool accessories. e-learning is a learning technology is relatively new in Indonesia. To simplify the term, the electronic learning is shortened to e-learning. The word consists of two parts, the 'e' is an abbreviation of 'electronica' and 'learning' which means 'learning'. The nature of e-learning is a form of conventional learning as outlined in a digital format through Internet technology. This system can be used in distance education or conventional education. Therefore, developing this model is not merely present the course material into the internet but need to be considered logically and holds the principle of learning. So e-learning means learning by using electronic tools and support services in implementation of e-learning to use the services of audio, video or computer device or a combination of the three.